(untitled) (International Journal of Environmental Sciences, 2025)
This study evaluates the effectiveness of intermittent vacuum-assisted closure (VAC) therapy in treating sacral pilonidal cysts in pediatric patients. Twenty-one patients underwent VAC therapy using an intermittent negative pressure mode for a duration of 14 days. Rapid granulation tissue formation and absence of infection were observed in all patients, indicating accelerated wound healing. The intermittent mode demonstrated advantages in terms of patient comfort, especially in younger children, while reducing the risk of skin irritation commonly associated with continuous suction. These findings suggest that intermittent VAC therapy is both effective and safe for use in pediatric practice. However, further studies are needed to explore long-term outcomes and determine the optimal frequency and duration of intermittent therapy sessions.